THE EFFECTIVENESS OF IMPLEMENTING RESTORATIVE JUSTICE TOWARDS CHILDREN AS PERPETRATORS OF BULLYING CRIMINAL ACTS AT PONTIANAK CITY POLICE OFFICE - Herlina Herlina; Plasma Versiana Mukti; Mega Fitri Hertini (NOMOI Law Review, 2026)
Bullying cases involving children, both as victims and perpetrators, occur relatively every year in Pontianak. This phenomenon raises concerns regarding the long-term impact on children's psychological and social development. Therefore, this study aims to analyze the effectiveness of the implementation of Restorative Justice against children as perpetrators of bullying crimes at the Pontianak City Resort Police and to identify the obstacles are faced by the Pontianak City Resort Police in the implementation of Restorative Justice against children as perpetrators of bullying crimes. The research method used is sociological juridical with an analytical descriptive approach. The data was obtained through in-depth interviews with police officers, the Pontianak City Child Protection Commission (KPAD), and related parties, and analyzed qualitatively and quantitatively. The research results show that the implementation of Restorative Justice at the Pontianak City Resort Police has been effective, marked by deliberations between the perpetrators, victims, and families to find the best solutions without formal judicial processes. The obstacles in the implementation of Restorative Justice were found in the difficulty of reaching agreements regarding compensation between the victim and the perpetrator. This research has a positive impact in the form of increasing public awareness and law enforcement officials regarding the importance of victim recovery and social reintegration of child perpetrators. Therefore, it is recommended to increase cross-sector cooperation to strengthen the implementation of Restorative Justice in child protection efforts in Pontianak City.